What has anthropology got to do with It? the interface between anthropology and tourism (2018)
Although there are obvious differences between anthropology and tourism in terms of goals and approach, anthropology and tourism share certain similarities as the two fields focus on specific spaces, paying attention to the ways of life of those whose lives are defined on such spaces. This article explores the interconnectedness that exists between anthropology and tourism, in order to establish the areas anthropology can enhance tourism and tourism studies. I have incorporated my experiences as an anthropologist and an academic in higher education institution, particularly experiences gained supervising the dissertations of postgraduate students in anthropology and tourism studies. I have discussed how the adoption of ethnographic approach in research projects carried out by students working on the area of tourism in the two disciplines brought insights into the experiences of tourists and members of the local communities at the tourist destinations. The article concludes that anthropology can enrich the discipline of tourism through its ethnographic enquiries, expertise and knowledge that are indispensable in the promotion of tourism and enhancing knowledge production in tourism studies.